La eficacia probatoria de la apropiación fraudulenta por medios electrónicos - Sisa Lema, Katherine Stefania (2024)
The thesis entitled ‘The evidentiary effectiveness of fraudulent appropriation by electronic means” explores the legal and technical challenges faced by the Ecuadorian justice system in investigating and punishing this computer-related crime. The research focuses on analyzing the elements of the criminality of the offense established in Article 190 of the Comprehensive Organic Criminal Code (COIP), complemented by a comparative study of the legislations of Ecuador, Spain, and Peru regarding the treatment of digital evidence. To address these challenges, interviews with prosecutors from the Citizen Patrimony Units were used, along with comparative tables and legal-doctrinal analysis. The findings highlight the lack of standardized protocols for handling digital evidence, the shortage of specialized computer experts, and difficulties obtaining banking information as critical factors affecting evidentiary effectiveness in these cases. The research concludes that the absence of clear protocols and insufficient specialized resources compromises the admissibility and validity of digital evidence in judicial proceedings, often leading to impunity in crimes of fraudulent appropriation by electronic means. This study highlights the urgent need to improve legal and operational